If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8n + 10 + -2n = 3n + -2 + 5n Reorder the terms: 10 + 8n + -2n = 3n + -2 + 5n Combine like terms: 8n + -2n = 6n 10 + 6n = 3n + -2 + 5n Reorder the terms: 10 + 6n = -2 + 3n + 5n Combine like terms: 3n + 5n = 8n 10 + 6n = -2 + 8n Solving 10 + 6n = -2 + 8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-8n' to each side of the equation. 10 + 6n + -8n = -2 + 8n + -8n Combine like terms: 6n + -8n = -2n 10 + -2n = -2 + 8n + -8n Combine like terms: 8n + -8n = 0 10 + -2n = -2 + 0 10 + -2n = -2 Add '-10' to each side of the equation. 10 + -10 + -2n = -2 + -10 Combine like terms: 10 + -10 = 0 0 + -2n = -2 + -10 -2n = -2 + -10 Combine like terms: -2 + -10 = -12 -2n = -12 Divide each side by '-2'. n = 6 Simplifying n = 6
| 8n+10-22=3n-2+5n | | -2x-10=4+5x | | -3-2x=18 | | 8(3w-7)=6(4w+5) | | -15+2m=-11 | | 1/6(10x-3)=7 | | -5+2m=11 | | (x/3)+(4x+6) | | 5x^2-38x+21= | | -15+10= | | 12*x+2*x+2=352 | | 12*x+2*x+2=0 | | 9-a/a+5=a/a+5 | | 14x+2=0 | | -6x^2-216x-600=0 | | 7x^0= | | (x-5)(2x+2)= | | (-9p^5q^3)(9pq^6)= | | 11/3c+12-c+1/c+4=c/3 | | 9x+3(x-4)=10(x+-5)+10 | | -15+15= | | -6-4c=-14 | | f(3)=4x^2+5x-6 | | 6-(x-3)=2(x+1) | | -16x^2+32x+10=0 | | 7/12x-5/3=7/4+5/6x | | -4.9x^2+30x+3=0 | | 0=2x^2-8x+13 | | 7/12x-5/3=7/4 | | -16x^2+30x+136=0 | | d/2+1/3=4d-1/12 | | 6000=20x+30y |